S. mentella maturity ogive in the Irminger Sea and Iceland waters - Saborido-Rey, Fran; Domínguez-Petit, Rosario; Garabana, Dolores; Sigurdsson, Thorsteinn (2005)
Poster.-- ICES Annual Science Conference, 20-24 September 2005, Aberdeen, UK As a part of a large project on Sebastes mentella in the North Atlantic, maturity processes have been studied in S. mentella in the Irminger Sea and and on the continental slope of Iceland. In this area, different phenotypes have been described as potentially different stocks, the so called oceanic and deepsea types. One of the reported differences between suggested stocks is based on different maturity ogives suggesting that deepsea type mature much larger than oceanic. In this paper the maturity ogives are estimated and the differences between maturity ogives analyzed, using different criteria both macroscopic and microscopic based in histological analysis. In addition and considering that most of the fish inhabiting Irminger Sea are sexualy mature, maturity ogives based on histological sections have been used to determine the maturity ogives in the previous spawning season, when recruit spawners become mature. Statistical analysis are performed to conclude that differences between phenotypes are lower than previosuly reported, and considering the sampling design and the year effect, no significant differences between them was found. Similarly, the comparison with data from the shelf of Iceland no differences between the two areas was found and that size at maturity in Iceland is lower than reported, based on macroscopic observations. The paper also suggests that using macroscopic observations on the maturity might be misleading due to the reproductive behaviour of redfish No